Teacher Expectations and Self-Determination Theory: Considering Convergence and Divergence of Theories - Hornstra, Lisette; Stroet, Kim; Rubie-Davies, Christine; Flint, Annaline (Educational psychology review, 2023)
Various theories from the field of educational psychology, including high expectation theory (HET) and self-determination theory (SDT), focus on the classroom conditions which facilitate students’ motivation, learning, and well-being. In the current paper, we aimed to breech the theoretical division between HET and SDT through a synthesis of both theories. We identified multiple areas of convergence and complementarity. The teaching practices that are theorized to support students’ motivation, learning, and well-being put forward by both HET and SDT show a high degree of conceptual overlap. Moreover, findings from both research fields suggest a gap between theory and practice: although the teaching principles put forward by both theories are believed to be effective for all students, not all teachers optimally apply these principles in their teaching or apply them equally for all classes or all students. Both theories acknowledge that teacher beliefs and contextual factors may account for this gap between theory and practice. In the paper, we put forward an integrative model to show how the two theories converge and complement each other. The integration of the two theories offers a way forward in terms of understanding and applying these two theoretical stances to the classroom.